Research progress on function and mechanism of long non-coding RNA in glioma: LncRNA in glioma: Function and mechanism - Tai, Feipeng; Zhao, Xueming (Cellular and Molecular Biology, 2024)
This review aimed to comprehensively summarize the role of long non-coding RNA (lncRNA) in gliomas, the most common malignant tumors in the central nervous system, and explore their potential clinical applications. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a systematic search using the PubMed database was conducted forty studies met the inclusion and exclusion criteria and were analyzed for type of intervention, the study’s design, participants’ demographics, and outcomes, including attrition. Gliomas, originating within the central nervous system, account for 40-45% of intracranial tumors. Despite advances in neurosurgical techniques, precise radiotherapy, and chemotherapy, the prognosis for glioma patients remains suboptimal. The review highlights the crucial regulatory role of lncRNA in gliomas. Differential expression of various lncRNAs, such as INHEG, SATB2-AS1, PSMB8-AS1, LINC01018, and SPRY4-IT1, has been observed in gliomas, suggesting their involvement in promoting or inhibiting tumorigenesis. Additionally, lncRNAs play roles in glioma characteristics such as proliferation, invasion, migration, angiogenesis, and the presence of glioma stem cells. The potential clinical applications of lncRNA in gliomas involve their association with tumor grading, diameter, metastasis, and family history. This review emphasizes the importance of understanding the molecular mechanisms involving lncRNA in gliomas. The identification of specific lncRNAs associated with gliomas provides potential molecular markers for diagnosis, differentiation, treatment, and prognosis evaluation. Further research is needed to uncover additional key lncRNAs and their underlying mechanisms, ultimately contributing to the improvement of glioma diagnosis and treatment.